1979
DOI: 10.1128/aem.37.5.892-896.1979
|View full text |Cite
|
Sign up to set email alerts
|

Production of Higher Alcohols During Indonesian Tapé Ketan Fermentation

Abstract: A study was made of the higher alcohols (fusel oils) produced during the Indonesian tape ketan fermentation using Amylomyces rouxii as the principal mold, alone or in combination with yeasts belonging to genera commonly found in the tape ketan fermentation (Endomycopsis, Candida, and Hansenula). Total fusel oils increased with length of fermentation. Fusel oils detected in the product distillate included isobutanol and isoamyl and active amyl alcohols. No n-propanol was detected. Isobutanol and isoamyl alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Meanwhile, the alcohol content in TK increased day by day during fermentation and was found as high as 4.6% (v/ v) after 7 days (Figure 3(c)) as also reported in reported in literature [25] . Figure 3(c) shows that the indicator follow similar trend till the TK ripe and vary from the alcohol response, when TK in the ripe and overripe stages.…”
Section: Figure 3 (B) the Color Indicator Response Vs Acidity (% W/v)...supporting
confidence: 87%
See 1 more Smart Citation
“…Meanwhile, the alcohol content in TK increased day by day during fermentation and was found as high as 4.6% (v/ v) after 7 days (Figure 3(c)) as also reported in reported in literature [25] . Figure 3(c) shows that the indicator follow similar trend till the TK ripe and vary from the alcohol response, when TK in the ripe and overripe stages.…”
Section: Figure 3 (B) the Color Indicator Response Vs Acidity (% W/v)...supporting
confidence: 87%
“…Humidity inside TK packaging has mainly resulted from the equilibrium between water contained in the TK and its headspace inside packaging since the headspace outside the packaging is not much affected due to the TK stored in tray with lit that has very limited or very low of water vapor transmission rate so that humidity outside packaging can be neglected. When alcohols are produced, by sugars metabolism without oxygen with the yeasts via fermentation process [25] , the color indicator starts to change to blue as water vapor also produces, and humidity inside packaging starts to increase drastically.…”
Section: The Indicator Response Towards the Fermentation Stagementioning
confidence: 99%
“…Utaminingdyah et al (2022) reported that tape from various types of rice (nonglutinous) inoculated with Lactobacillus plantarum Dad-13 produced lactic acid levels, acetic acid, and ethanol, respectively, at 0.21-0.53%, 0.14-0.35%, and 0.81-0.91%. Cronk et al (1979) showed that Amylomyces rouxii, separately or in combination with different yeasts, yielded a higher range of alcohols, including isobutanol (2-methyl-1propanol), 2-methyl-1-butanol and isoamyl alcohol (3-methyl -1-butanol).…”
Section: Preference Levelmentioning
confidence: 99%
“…The production of glucose, lactic acid, and ethanol gives a bit of alcohol taste and sour-sweet taste. Cronk et al (1979) stated that A. rouxii, with or combined with a different yeast, produces various kinds of alcohol in higher amount, including isobutanol (2-methyl-1-propanol), 2-methyl-1-butanol and isoamyl alcohol (3-methyl-1-butanol). Each of the alcohol type has different sensory characteristics, however, the concentration which can influence the sensory characteristics is not yet known.…”
Section: Rice Tape and Cassava Tape Sensory Profilesmentioning
confidence: 99%